Pengaruh Komitmen dan Budaya Organisasi Terhadap Engagement Karyawan: (Studi pada Karyawan DC. Yogya Group Cabang Cikoneng) - Windi Ayu Meliana (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This study aims to determine the effect of commitment and organizational culture on employee engagement at DC Yogya Group Cikoneng Branch, Tasikmalaya. The method used is a case study, data obtained through questionnaires to the number of employees working at DC Yogya Group Cikoneng Branch. Sampling using saturated sample technique and the method of analysis used is multiple linear regression analysis method. From the results of the study indicate that commitment, organizational culture and employee engagement are included in the low classification. Simultaneously commitment and organizational culture have a significant effect on employee engagement at DC Yogya Group Cikoneng Branch. Partially, the commitment variable has a significant effect on employee engagement at the DC Yogya Group Cikoneng Branch, and the organizational culture variable has a significant effect on employee engagement at the DC Yogya Group Cikoneng Branch.